Spinal infection caused by Coxiella burnetii - Sumin Yang; Bai Xue; Xiaowen Hu; Weidong Zhou; Minglei Zhang; Mingwei Zhao (BMC Infectious Diseases, 2023)
Abstract Background Spinal infection caused by Coxiella burnetii is rare and difficult to diagnose. Here we reported a case of spinal infection from Coxiella burnetii detected by the metagenomic next-generation sequencing (mNGS). Case presentation A 66-year-old male farmer with no medical history reported severe sharp low back pain, numbness and lower limb weakness for three years. Magnetic resonance imaging (MRI) revealed bone destruction and spinal cord compression within L1 and L2. mNGS testing showed that the inspected specimen collected from spinal lesion was detected positively for Coxiella burnetii. After receiving the combined treatment of antibiotic therapy and surgical intervention, the patient recovered well, and the sagittal MRI showed that vertebral edema signals disappeared and the graft of bone fused 16 months after surgery. Conclusion The mNGS may be benefit for early diagnosis and intervention of non-specific spinal infection, and future studies should validate its effectiveness for clinical use in spinal infections. Additionally, antibiotic therapy combined with surgical intervention plays an important role on the treatment of spinal infection caused by Coxiella burnetii.